Results of the treatment with osseointegrated dental implants in surgery - Oviedo Perez Perez; Eugenio Velasco Ortega; Orlando Rodriguez; Lleila González Olivares (Editorial Ciencias Médicas, 2014)
Objective: To evaluate the results of treatment with osseointegrated dental implants in surgery. Methods: A prospective longitudinal study of 802 patients with 2 165 implants, in the provincial teaching dental clinic of Santiago de Cuba and the Dental School of Havana from 2000 to 2009. The surgical techniques evaluated were length and diameter of the implants, surgical and postsurgical complications. The results of treatment were evaluated as survival and failure rates. Results: The dental implants survived in 705 patients for 87.9 % and failed in 97 for 12.1 %; 2 165 dental implants were placed, 2 055 were effective for 94.9 % and 110 failed for 5.08 %. There are not significant differences among outcomes, depending on the used surgical techniques. Failure was mostly frequent in 10 mm implants, accounting for 34.9 % and in 8 mm for 13.1 %. Effectiveness increases as the diameter increases. In intraoperative complications, failure was greater in osseous perforations for 92.6 %, instability for 86 % and bone dehiscence for 57.4 %. In the postsurgical phase, it was noticeable that the implants of 100% of patients with pain failed. Conclusions: In the surgical stage, a strong relation between outcomes and length, diameter, and surgical and postsurgical complications was found.   Keywords: dental implants, surgical technique, implantology, effectiveness, failure, length, diameter.